How a Servant-Leadership Attitude Affects Discharge Planning Efficiency - Puspita, Reny Anggraeni Dwi; Nursalam, Nursalam; Kartini, Yanis (Poltekkes Kemenkes Surakarta, 2024)
Background: Discharge planning is one way in which leadership styles can motivate nurses to up their game and provide better care to patients. Examining how a servant leadership style affects the success of discharge planning initiatives is the primary goal of this study. Methods: The initial part of this mixed-method study involved doing qualitative research using an exploratory descriptive methodology with seven participants at Surabaya's Bhakti Dharma Husada Hospital. Research using quantitative methods and a quasi-experimental design is the second phase. Using a purposeful sampling technique, 114 nurses from the inpatient population at Bhakti Dharma Husada Hospital Surabaya participated in the study. Of this, 57 were assigned to the intervention group and 57 to the control group. Results: The first stage of the study produced a servant leadership module for the head of the room. In the second stage, based on the paired sample t-test, there was an effect after the intervention was given while entering the hospital (ρ = 0.000), during treatment (ρ = 0.000), and before leaving the hospital (ρ = 0.000). In the independent sample t-test, there was a significant difference in the post-test mean between the intervention and control groups during entering the hospital (ρ = 0.000), during treatment (ρ = 0.000), and before leaving the hospital (ρ = 0.000) on the performance results of the discharge plan. Conclusion: The ward head at Bhakti Dharma Husada Hospital Surabaya can use the servant leadership module and intervention to improve the performance of discharge planning from the time a patient enters the hospital to the time they leave.